Jawbone mesenchymal stromal cells attenuate acute inflammation via hematopoietic niche reinforcement - Wang, Xinyu; Chen, Qianye; Sun, Jiping; Huang, Zihan; Zhang, Zijian; Lu, Tingwei; Huang, Xiangru; Sun, Siyuan; Liu, Yuanqi; Pan, Houwen; Mei, Li; Cooper, Paul R.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe bone marrow microenvironment, comprising various cell types and molecular signals, finely orchestrates the self‐renewal and lineage commitment of hematopoietic stem cells (HSCs). Although most investigations have centered on mesenchymal stem cells (MSCs) from long bones, the distinct properties and immunoregulatory functions of craniofacial bone marrow derived MSCs remain largely unexplored. Notably, jawbone MSCs not only exhibit a robust capacity for promoting hematopoietic regeneration but also offer therapeutic potential in infectious diseases.MethodsUsing an optimized enzymatic digestion protocol, we obtained a highly viable single‐cell suspension from mouse jawbone in vitro. Single‐cell sequencing was then performed to explore the interactions between jawbone MSCs and HSCs, while tissue immunofluorescence clarified their spatial distribution. In vitro osteogenic and adipogenic differentiation assays confirmed the multilineage potential of jawbone MSCs. A biomimetic co‐culture system, designed to emulate the bone marrow niche, was employed to assess the impact of jawbone MSCs on HSC differentiation, which was evaluated via flow cytometry. Mechanistic insights into HSC changes were gleaned from RT‐qPCR and cellular immunofluorescence. Subsequently, an LPS‐induced acute infection model was established to evaluate the therapeutic efficacy of jawbone MSCs. Finally, comprehensive analysis of single‐cell sequencing data, in conjunction with RT‐qPCR findings, elucidated the regulatory pathways through which jawbone MSCs promote hematopoiesis.ResultsSingle‐cell sequencing revealed a robust interaction between jawbone MSCs and HSCs. Tissue immunofluorescence demonstrated that in the mouse jawbone, MSCs and HSCs were located in close spatial proximity. In vitro osteogenic and adipogenic induction experiments showed that jawbone MSCs possess considerable multilineage differentiation potential. Co‐culture assays further indicated that jawbone MSCs induce HSCs to differentiate into various immune cell types, particularly promoting B cell generation. RT‐qPCR and immunofluorescence assays confirmed that pivotal transcription factors, such as PAX5, were activated in B cells. In an in vivo infection model, jawbone MSCs exhibited significant anti‐infective capabilities, effectively reducing mortality and systemic inflammation in infected mice. A deeper analysis of the single‐cell sequencing data revealed that jawbone MSCs mainly facilitate hematopoiesis by secreting CXCL12.ConclusionThrough single‐cell sequencing, in vitro multilineage induction, co‐culture systems, and a mouse model of LPS‐induced acute infection, this study systematically elucidates the close interplay between jawbone MSCs and HSCs, as well as their pivotal roles in immune modulation and anti‐infective responses. The findings demonstrate that jawbone MSCs not only exhibit robust multilineage differentiation potential but also secrete CXCL12 and activate key B cell transcription factors (such as PAX5). This process significantly promotes HSC differentiation into B cells, improves survival rates in infected mice, and attenuates systemic inflammation. These results establish a strong foundation for further investigation into the applications of jawbone MSCs in immune regulation and disease therapy.